2020
DOI: 10.2298/psi190730013s
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of emotion regulation difficulties in the relationship between social anxiety and problematic internet use

Abstract: This study aimed to examine whether there is a mediating role of emotion regulation difficulties in the relationship between social anxiety and problematic Internet use (PIU). The sample consisted of 297 participants (147 [49%] males; aged from 18 to 24 years), who were university students studying sport sciences in four universities in Turkey. Data were obtained using the Liebowitz Social Anxiety Scale, Internet Addiction Scale, and Scale of Difficulties in Emotional Regulation. Structural Equation Modeling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…There are also nonexistence of statistically significant differences at the Internet addiction level among the Hashemite university students, due to gender and it appears from the result that students who have the desire to be addicted to the Internet and will use the Internet for long hours, regardless of their social type or gender will find the necessary time to meet their full needs satisfied by the Internet use. The current findings agree with the study results of Kürşad et al (2020); Mustafa et al (2018); Tras and Gökçen (2020) where its results indicated nonexistence of differences in the social anxiety, due to gender.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…There are also nonexistence of statistically significant differences at the Internet addiction level among the Hashemite university students, due to gender and it appears from the result that students who have the desire to be addicted to the Internet and will use the Internet for long hours, regardless of their social type or gender will find the necessary time to meet their full needs satisfied by the Internet use. The current findings agree with the study results of Kürşad et al (2020); Mustafa et al (2018); Tras and Gökçen (2020) where its results indicated nonexistence of differences in the social anxiety, due to gender.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the widespread of Internet addiction, the results of Alshehri et al (2015) study indicated that Internet addiction is a common problem with about (45.3%) of students who suffer from the Internet addiction, as the study sample. The study results of Kürşad et al (2020); Dorani et al (2015) also indicated a correlation between the Internet addiction and social anxiety and the nonexistence of differences in the addiction degree between males and females (Mustafa et al, 2018) and this confirmed by the study results of Harman, Hansen, Cochran, and Lindsey (2005) which indicated a correlation between Internet addiction and the high level of social anxiety and violence.…”
Section: Internet Addictionmentioning
confidence: 81%
See 3 more Smart Citations